Multi-Purpose Trees Species Damage Index: Case Study of Wan Abdul Rachman Forest Park Utilization Block, Lampung - Rahmat Safe'i; Rico Andrian; Tri Maryono; Rahmat Safei; Rahmat Safe’i (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
The Wan Abdul Rachman (WAR) Forest Park (TAHURA) Utilization Block is a location that can be utilized by the community, especially its non-timber forest products. Utilization of non-timber forest products is the type of Multi-Purpose Trees Species (MPTS). On the other hand, many trees were damaged due to this utilization. This study aimed to obtain the damage index (IK) of MPTS types in the TAHURA WAR utilization block. Data was collected by assessing the IK of trees based on the Forest Health Monitoring (FHM) method on five cluster plots of FHM. Data analysis was carried out using the IK value formula. The results showed that there were 13 types of MPTS found in the TAHURA WAR utilization block; with the range of IK values for each kind of MPTS as follows: Durio zibenthinus (0.0-6.1), Persea americana (1.4-6.5), Parkia speciosa (0.0-5.8), Archidendron pauciflorum (1.5-6.1), Gnetum gnemon (0.0-6.1), Hevea brasiliensis (1.4-6.1), Theobroma cacao (1.4-5.0), Mangifera indica (1.6-4.3), Sygyzium malaccensis (1.6-4.6), Arthocarpus heterophyllus (1.6-5.8), Sygyzium aqueum (1.4-4.3), Sygyzium aromaticum (1.5-3.8) and Tectona grandis (1.6-4.9). The location influences the size of the IK value, type and severity of tree damage found. Thus, the average IK values for each kind of MPTS in the TAHURA WAR utilization block were Hevea brasiliensis (4.3), Artocarpus heterophyllus (4.2), Archidendron pauciflorum (4.1), Theobroma cacao (4.0), Tectona grandis (3.8), Persea americana (3.5), Parkia speciosa (3.5), Durio zibenthinus (3.4), Sygyzium malaccensis (3.4), Gnetum gnemon (3.2), Sygyzium aqueum (2.9), Mangifera indica (2.7) dan Sygyzium aromaticum (2.4).